Anteseden Innovation Capability yang Dimediasi Digital Talent dan Value Co Creation - Agustin Ratna Sari; B. Medina Nilasari, Dita Oki Berliyanti (SEIKO : Journal of Management & Business, 2025)
This study aims to explore the relationship between human resources digital transformation (HRDT), digital talent, employee entrepreneurship, shared value creation, and innovation capability in the context of Micro, Small, and Medium Enterprises (MSMEs) in Jakarta. In the Industry 4.0 era, digital technology is becoming a major driving force that is changing the way organizations operate and create value. This research identifies that the digital transformation of HR not only improves innovation capabilities, but also plays an important role in attracting the digital talent needed to drive sustainable innovation. In addition, employee entrepreneurship and value co-creation are considered key factors in enhancing organizational innovation capabilities. Through a comprehensive methodological approach, this study proposes a conceptual framework that highlights the strategic role of digital talent and shared value creation in supporting the digital transformation process. The research results are expected to provide theoretical and practical contributions for academics and practitioners in understanding the dynamics of the relationship between these variables and their implications for the competitiveness of MSMEs in an increasingly competitive digital market. Keywords: Human Resource Digital Transformation, Digital Talent, Employee Entrepreneurship, Value Co Creation, Innovation Capability